K-Selection as Microbial Community Management Strategy: A Method for Improved Viability of Larvae in Aquaculture - Vadstein, Olav; Attramadal, Kari J. K.; Bakke, Ingrid; Olsen, Yngvar (Frontiers in Microbiology, 2018)
Aquaculture is the fastest growing food industry in the world, and marine fish is a significant source of protein, essential long-chain omega 3 fatty acids, and micronutrients for the increasing human population. A bottleneck in marine aquaculture is the production of high quality juveniles. For many species, survival of larvae is typically as low as 10-15%, and this is an indicator of suboptimal conditions. Substantial evidence indicate that detrimental larvae-microbiota interactions are a major cause of the poor performance and viability of larvae. Thus, there is a need for microbial management strategies in cultivation of marine fish larvae. Disinfection and probiotics are the most studied and used microbial management methods so far. However, most of these studies overlook the role of mutualistic relationships between microbes and hosts in healthy hosts, and do not propose and examine methods to steer towards such relationships. Based on ecological theory and a number of experiments, we find support for the hypothesis that current practice in aquaculture generally select for r-strategic, opportunistic microbes that result in detrimental host-microbiota interactions. Based on this, the challenge is to develop technology and methods for system management that creates a K-selected microbial community, and by this mean select against r-strategic opportunists. Here we summarize experiments showing that: 1. K-selection strategies results in a different water microbiota with less opportunists, 2. this influences the microbiota of the fish larvae, and 3. the larvae cultivated in water inhabited by K-selected microbiota perform better. Improved performance of larvae includes improved appetite, earlier onset of and faster growth, increased survival, and increased robustness to stress. K-selection as a method for management of the microbial community is a robust approach that allows steering of host-microbiota interactions in larviculture towards mutualism, and it could also be applicable for young stages of other domestic animals.